The Effect of Isometric Handgrip Therapy Towar Blood Pressure on Hypertension Patients in the Work Area OF batangkuis Public Health Center - Dian Anggri Yanti; Dila Rizkia (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2022)
Hypertension is a condition when the systolic blood pressure (BP) is greater than 140 mmHg and the diastolic blood pressure is greater or above 90 mmHg. According to the America Heart Association (AHA), the America population aged over 20 years who hypertension has reached 74.5 milion people, but almost 90-95% of cases have no known cause. Hypertension has the potential to cause fatal complications end opens up greater opportunities for patients to suffer from storke, coronary heart disease, have a high risk of kidney failure, heart failure, and eye damage. Physical activity that used to lower blood pressure is the Isometric Handgrip Exercise which done with static exercises on contracting muscles, without any changes in muscle length or hand joint movement. Objective : This study aims to determine the effect of isometric handgrip therapy on blood pressure in patients with hypertension in the working area Batang Kuis Health Center. Method : This study uses a quasi-experimental quantitative method using a pre-test post-test design with a sample 29 people. The measuring instrument used in this research is the observation sheet. Data analysis was carried out using the paired t-test sample. Result: It seen the paired t-test of blood pressure before and after giving of isometric handgrip therapy, the mean value is 4.034 with std. Devitation 1.267 with a 95% confidence level with a value of 0.05 from a significant value of 2 tiles 0.000 or 0.000 < 0.05. Thus, it concluded that there is an effect of giving isometric handgrip therapy on reducing blood pressuer in hypertension patients in the Batang Kuis Health Center.